EFFECTIVENESS OF SOME CARBAMATE INSECTICIDES FOR REPELLING A PEST BIRD (LONCllURA STRIATA) TO REDUCE EAR DAMAGE OF FOX-TAIL MILLET (Biological Sciences - PJSIR, 1995)
A field trial was conducted at RARS, Hathazari, Chittagong with three carbamate insecticides, isoprocarb, carbosulfan and carbaryl replicated 3 times during both the 1988-89 and 1990-91 cropping seasons to test their efficacy in repelling the pest bird, Lonchura striata, and to reduce ear damage of fox-tail millet. Two applications of these insecticides on ripening millet at 15 and 7 days before harvest reduced bird damage and increased yield significantly as compared to control. Among the insecticides, isoprocarb was the best, followed by carbosulfan and carbaryl in both seasons.